Microbiology in the Field: Construction and Validation of a Portable Incubator for Real-Time Quantification of Coliforms and Other Bacteria - Wight, Jordan; Varin, Marie-Pierre; Robertson, Gregory J.; Huot, Yannick; Lang, Andrew S. (Frontiers in Public Health, 2020)
Performing microbiological assays on environmental samples in field settings poses logistical challenges with respect to the availability of suitable equipment or the ability to get samples to the laboratory in a timely fashion. For example, the viability of some bacteria can decrease greatly between sampling and arrival to the laboratory for processing. We developed and constructed rugged, reliable, and cost-effective portable incubators that were used by 10 independent field teams to perform microbiological assays on surface water samples from lakes across Canada. Rigorous testing and validation of our incubators ensured that incubation conditions were consistent within and across all 10 field teams and 2 sampling years. Samples from all sites were processed in duplicate and bacterial counts were highly repeatable within and across sampling teams. Bacterial counts were also found to be statistically equivalent to counts obtained with standard laboratory techniques using a conventional incubator. Using this method, thermotolerant coliforms (TTCs) and Escherichia coli were quantified from 432 lakes, allowing comparison to both historical datasets that relied on TTCs and those following current guidelines that use E. coli counts. We found higher loads at the shoreline than the middle of lakes and different patterns between ecozones. E. coli was not frequently detected, but many lakes exceeded Canadian guideline values for activities such as swimming and some even exceeded the guideline value for secondary recreational activities such as boating. To the best of our knowledge, this is the largest bacteriological water quality assessment of freshwater lakes to date in terms of both spatial scale and the number of lakes sampled. Our incubator design can be easily adapted for a wide variety of researcher goals and represents a robust platform for field studies and other applications, including those in remote or low-resources settings.